Improving Documentation of Sleep Assessments in Attention Deficit Hyperactivity Disorder (ADHD) Clinics at Havering Child and Adolescent Mental Health Service - Nafiz Imtiaz; Trilok Rana (BJPsych Open)
Aims: Sleep is an essential component of mental well-being. Many patients presenting in the ADHD clinic report sleep issues, which stem from underlying physical or mental health conditions, or as side effects of prescribed medications. These sleep disturbances, if unaddressed may exacerbate existing mental health issues. It can often be challenging to complete a thorough assessment of sleep disturbance in an ADHD clinic in a limited time. Essential components of documentation of sleep assessment were identified from National Institute for Health and Care Excellence (NICE) guidance. Our aim was to achieve 100% documentations containing all essential components of sleep assessment in the ADHD clinic by August 2024.